Traits of plant communities in fragmented forests: the relative influence of habitat spatial configuration and local abiotic conditions. (26th February 2014) - Kimberley, Adam; Alan Blackburn, G.; Duncan Whyatt, J.; Smart, Simon M.; Canham, Charles
Summary The plant trait composition of forest fragments is thought to be partly determined by forest spatial properties, although the relative importance of habitat configuration and local abiotic drivers is poorly understood. To address this issue, large‐scale habitat extent data were combined with detailed field survey information for temperate broad‐leaved deciduous forest patches to quantify the relative effects of spatial and abiotic filters on plant community mean trait values. Local conditions such as shade and soil fertility had the largest effect on mean trait values, but aspects of habitat configuration also had significant partial effects on a number of traits. Mean trait values within older forest patches were more strongly influenced by forest spatial configuration than in younger patches. Synthesis. Results indicate that, in addition to the effects of greater light availability and competition in small patches and at forest edges, aspects of habitat configuration such as patch size and isolation are themselves important factors limiting the occurrence of forest specialist species. Large areas of core forest habitat contain a greater proportion of rare, poor dispersing species, although these effects were less visible in more recently established forest. This highlights the importance of maintaining existing large and old forest patches as a refuge for forest specialist plants. The results of this comparison of spatial and abiotic variables suggest that controlling the spatial properties of forest patches is likely to prove an effective way of managing plant species diversity, provided that sites with appropriate abiotic conditions are chosen.